Resistance of Eucalyptus species, progenies and provenances to Puccinia psidii Winter - de Oliveira de Carvalho, Aldir; Couto Alfenas, Acelino; Antônio Maffia, Luis; Goréte Ferreira do Carmo, Margarida (Pesquisa Agropecuaria Brasileira, 1998)
Rust resistance levels of two Eucalyptus citriodora, three E. pellita, three E. urophylla, and three E. cloenziana provenances were determined. The number of sori and the degree of disease severity/2.4 cm2 of foliar area were evaluated on artifitially inoculated plants. Also the proportions of rusted branches and leaves on the same plants naturally infested in the nursery were considered. Significant variations were detected among species, provenances and progenies. Differences were as well detected between individuals belonging to the same species, provenances or progeny. Results from natural infection were similar to those obtained from artificial inoculation, thus indicating that selection of resistant Eucalyptus genotypes may be successfully carried out in the nurseries if inoculum pressure and climatic conditions are favourable to the fungus. All the provenances of E. citriodora, E. urophylla and E. pellita, besides the D1 progeny of E. cloenziana were resistant. The remaining provenances and progenies of E. cloeziana were susceptible to P. psidii.